Haiti : beleaguered nation of the Caribbean : who can deny its people assistance? : a report (Caribbean Human Rights Network BridgetownBB, 1993)
Provides some historical background on Haitian migrations and a chronology of the Haitian Refugee Mission. Reviews societal conditions of the Haitians in the Bahamas and makes recommendations for consideration and adoption by the Bahamas Government. Examines the conditions in Haiti as a cause of migration. Posits that for a lasting solution to be found, substantial assistance in both expertise and resources must be provided by major world political and economic powers without delay.
DC